Cost-effectiveness of recombinant tissue-type plasminogen activator for acute ischaemic stroke with unknown time of onset: a Markov modelling analysis from the Chinese and US perspectives. Issue 11 (14th November 2022) - Zhao, Songfeng; Cheng, Yuhong; Tong, Xin; Han, Mingyang; Ji, Linjin; Che, Yuxiong; Hu, Weiwu; Liu, Aihua
Abstract : Objective: The effectiveness of MRI-guided intravenous recombinant tissue-type plasminogen activator (r-tPA) for acute ischaemic stroke (AIS) with an unknown time of onset has been demonstrated by the WAKE-UP Trial. We aim to evaluate its long-term cost-effectiveness from the perspective of Chinese and US healthcare payers. Methods: A combination of decision tree and Markov model was built to project lifetime costs and quality-adjusted life-years (QALYs) associated with intravenous r-tPA or placebo treatment. Model inputs including the transition probabilities, costs and utilities were derived from the WAKE-UP Trial, similar cost-effectiveness studies and other published sources. To compare intravenous r-tPA to placebo, we calculated incremental costs, incremental QALYs and incremental cost-effectiveness ratio (ICER). One-way sensitivity, probabilistic sensitivity and subgroup analyses were performed to evaluate uncertainty in the results. Results: In China, intravenous r-tPA gained an additional lifetime QALY of 0.293 with an additional cost of the Chinese Yuan (¥) of 7871 when compared with placebo, resulting in an ICER of ¥26 870 (US$3894)/QALY. In the USA, intravenous r-tPA yielded a higher QALY (difference: 0.430) and lower cost (difference: ¥−4563) when compared with placebo. In probabilistic sensitivity analyses, intravenous r-tPA had a 97.8% and 99.8% probability of being cost-effective or cost-saving in China and the USA, respectively. These findings remained robust under one-way sensitivity and subgroup analysis except for patients with a National Institute of Health Stroke Scale Score of less than 4, between 11 and 16, and over 16. Conclusions: MRI-guided intravenous r-tPA for patients with AIS with an unknown time of onset is cost-effective in China and cost-saving in the USA.